Gottes Reue. Zum theologischen Verständnis Gottes als Subjekt der hebräischen Wurzel nhm - Balzer, H. R. (Verbum et ecclesia, 1991)
The Regret of God. On the theological relevance of God as subject of the Hebrew verb nhm Professor JA Heyns and others regard God's 'regret' of His own plans or actions in the Old Testament, expressed by the Hebrew verb nhm , as part of the dogmatic problem of ‘anthropomorphism’ against general presupposition like His immutability. However, an exegetical investigation indicates that this virtual aporia as well as the supposed polysemy of nhm , i.e. ‘regret’ and ‘comfort’, is mainly caused by our own unspoken ‘ontological’ and therefore ‘absolute’ and ‘objective’ view on God. In a non-ontological perspective, focusing on concrete relations, the ‘regret’ of God must on the contrary be seen as expression for the stability and continuity of the deus absconditus towards humankind.